Stacking faults in silicon carbide - Iwata, H.P; Lindefelt, U; Öberg, S; Briddon, P.R (Physica. B, Condensed matter, 2003)
We review of our theoretical work on various stacking faults in SiC polytypes. Since the discovery of the electronic degradation phenomenon in 4H–SiC p–i–n diodes, stacking faults in SiC have become a subject of intensive study around the globe. At the beginning of our research project, the aim was to find the culprit for the degradation phenomenon, but in the course of this work we uncovered a wealth of information for the general properties of stacking faults in SiC. An intuitive perspective to the diverse nature of stacking faults in SiC will be given in this conference report.